2018
DOI: 10.18052/www.scipress.com/jhpr.3.13
|View full text |Cite
|
Sign up to set email alerts
|

Response of Mung Bean Crop to Different Levels of Applied Iron and Zinc

Abstract: Fertilization of Mung bean (Vigna radiataL) is one of the most crucial management technique which effects crop growth and yield. Therefore the present study was carried out at Agricultural Research Station Kohat under rain fed conditions during spring 2017, to assess the response of mung bean (Vigna radiateL.) to three levels of iron (0, 2 and 5 kg ha-1) and three levels of zinc (0, 5 and 10 kg ha-1). The experiment was laid out in randomized complete design with split plot arrangement and replicated three tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
2
3
0
1
Order By: Relevance
“…However, combined application of micronutrient was resulted superior straw yield of mungbean over their single application. Similar observation was corroborated by Jamal et al (2018); . The following growth and yield contributing characters are played vital role to achieve the improved yield of mungbean.…”
Section: Yields Of Mungbeansupporting
confidence: 85%
“…However, combined application of micronutrient was resulted superior straw yield of mungbean over their single application. Similar observation was corroborated by Jamal et al (2018); . The following growth and yield contributing characters are played vital role to achieve the improved yield of mungbean.…”
Section: Yields Of Mungbeansupporting
confidence: 85%
“…La tasa de crecimiento del cultivo (TCC) (Figura 6) que indica la eficiencia productiva de la biomasa por unidad de superficie ocupada (suelo) a través del tiempo (Santos et al, 2010), este trabajo fue estadísticamente similares, Pingoliya et al (2014) mencionan que la aplicación de 2 kg ha -1 de sulfato ferroso incrementó la biomasa, producción y rendimiento de Cicer arietinum. El rendimiento con las dosis de Fe y Zn no mostraron diferencias estadísticas, el Fe en las dosis de 450 g, ha referido un mayor rendimiento con 28 t ha -1 en comparación con el testigo (Figura 7), resultados diferentes se presentaron en el cultivo de Vigna radiata donde las dosis de 5 kg ha -1 de Fe contribuyó al máximo rendimiento (Jamal et al, 2018).…”
Section: Resultados Y Discusiónunclassified
“…This indicated that mungbean responded better to zinc application for soil even at higher rates without showing the symptoms of zinc toxicity. In an earlier study Jamal et al [17] reported that "mungbean responded upto application of zinc at 10 kg/ha". "Zinc also has significant role in primordia initiation, indole-acetic acid synthesis and partitioning of food material from leaves to reproductive parts which ultimately results in good fruiting" [18,19].…”
Section: Discussionmentioning
confidence: 99%